Antiviral innate immunity in myocarditis: mechanisms and emerging therapeutics - Caleb Hammons; Athul Mohanram; Preston Nguyen; Wenting Lu; Betty Jacobs; Xian Chang Li; Zhiqiang Zhang; Junji Xing (Experimental & Molecular Medicine, 2026)
Abstract Antiviral innate immunity is a decisive determinant of whether cardiotropic viral infection resolves or progresses to myocarditis and deadly heart failure. Viral myocarditis (VM) remains a leading cause of sudden death in children and young adults, yet its human pathophysiological mechanisms remain incompletely understood and effective therapies are limited. In this Review, we map the cellular and molecular logic of cardiac antiviral innate immunity from first sensing to therapeutic opportunity and synthesize how these responses set the myocardial ‘inflammatory set point’ across cardiac-resident cells and recruited innate immune cells. We highlight RNA- and DNA-sensing immune signaling pathways that detect cardiotropic RNA and DNA viruses to collectively shape viral control and heart injury during VM. Finally, we connect mechanisms to translation by summarizing emerging biomarkers and clinical trials and by proposing a phase- and etiology-guided therapeutic framework that pairs antiviral immunomodulation with timely restraint of innate proinflammatory amplifiers to limit heart damage and prevent progression from VM to heart failure. This review will provide a roadmap of antiviral innate immunity to accelerate mechanistic discovery and targeted therapy for VM and virus-associated cardiovascular diseases.